Executive–Legislative Relations in Appointing the Indonesian National Police Chief - Hisyam Hisyam; Rahmatul Hidayati; Budi Parmono (Academia Open, 2026)
General Background The post-amendment 1945 Constitution establishes Indonesia as a presidential system with the President holding supreme executive authority, supported by a framework of checks and balances. Specific Background Within this framework, Article 11 paragraph (1) of Law No. 2 of 2002 requires approval from the House of Representatives in appointing the Chief of the Indonesian National Police, generating sustained constitutional and theoretical debate. Knowledge Gap Existing discussions have not sufficiently clarified whether this approval mechanism constitutes a limitation on presidential authority or operates as a confirmation instrument consistent with presidentialism. Aims This study aims to examine the conformity of the DPR approval requirement with presidential system principles under the 1945 Constitution and to analyze its implications for presidential executive authority. Results Using normative legal research with legislative, conceptual, and historical approaches, the study finds that DPR involvement functions as a confirmation power within the checks and balances mechanism rather than a transfer or reduction of executive authority. Novelty The study demonstrates that the approval mechanism preserves the President’s role as the sole proposer of candidates while situating legislative participation within constitutionally justified oversight. Implications These findings affirm that DPR approval strengthens public accountability and institutional legitimacy without altering the fundamental structure of Indonesia’s presidential system, thereby supporting constitutional consistency and governance stability. Highlights: DPR participation operates as a confirmation mechanism rather than an appointment authority. Presidential control over national security leadership remains constitutionally intact. Legislative involvement contributes to accountability and institutional legitimacy. Keywords : Presidential System, Checks and Balances, DPR Approval, Executive Authority, Police Chief Appointment